Pengaruh Edukasi dan Pemberian Teh Bunga Telang Terhadap Penurunan Tekanan Darah pada Lansia Dengan Hipertensi di Posyandu Cening Kelas Lansia Kampung Warga Indah Jaya Kecamatan Banjar Agung Kabupaten Tulang Bawang Tahun 2024 - Karani, Wayan Noti; Kustiani, Ai; Jayadi, Ajib (Journal of Education Technology Information Social Sciences and Health, 2025)
Background: Hyperrternsiron irs a common heralth irssuer among ther erlderrly and can lerad to varirous complircatirons. Accordirng to ther SKIr (Irndonersiran Heralth Survery) data, ther prervalerncer of hyperrternsiron irn Irndonersira among thoser agerd ≥18 yerars baserd on doctor diragnosirs irs 8.6%, and hyperrternsiron baserd on merasurermernt rersults irs 30.8% across all provirncers irn Irndonersira. Objective: Thirs study airms to analyzer ther erfferct of erducatiron and ther admirnirstratiron of butterrfly pera tera on rerducirng blood prerssurer irn ther erlderrly at Posyandu Cernirng, Warga Irndah Jaya. Methods: Thirs study userd a quantirtatirver approach wirth a quasir-erxperrirmerntal dersirgn and a oner-group prer-terst and post-terst merthod. Ther erlderrly populatiron at Posyandu Cernirng numberrerd 70, from whirch a sampler of 35 was serlercterd for knowlerdger erducatiron and 33 for ther admirnirstratiron of butterrfly pera tera. Ther erducatironal irnterrverntiron lasterd oner day, and butterrfly pera tera was admirnirsterrerd overr 7 days. Statirstircal analysirs was conducterd usirng ther T-terst, and ther data showerd an irncreraser irn knowlerdger post-irnterrverntiron, wirth a p-valuer 0.05. Systolirc blood prerssurer dercreraserd from an averrager of 152.42 mmHg to 130.61 mmHg (p 0.05), and dirastolirc blood prerssurer dercreraserd from 96.06 mmHg to 85.45 mmHg (p 0.05) post-irnterrverntiron. Ther sirgnirfircant rerductiron irn blood prerssurer irndircaters that nutrirtiron erducatiron and ther admirnirstratiron of butterrfly pera tera arer erfferctirver irn managirng hyperrternsiron irn ther erlderrly. Thirs study rercommernds an erducatironal approach to irmprover knowlerdger and heralthy berhaviror among ther erlderrly, and suggersts ther poterntiral of butterrfly pera tera as an alterrnatirver irn managirng hyperrternsiron.